When I am an old woman I shall wear purple : an anthology of short stories and poetry - Martz, Sandra (Papier-Maché Press, 1987)
"This enchanting collection of writings and photographs evokes the beauty, humor and courage of women living in their later years and tells of the endearing moments of joy--and passion--to be found in the rich and varied world of midlife and beyond. An award-winning anthology that takes a refreshing look at issues of aging in a society that glorifies youth. Over 1.6 million copies of the anthology have been sold across the United States. This groundbreaking collection was one of the first non-clinical and positive books on women and aging, and was written by older women themselves. It challenged stereotypes and confronted the invisibility of older women in America"--Publisher.